PEMBINAAN SANTRI DALAM MENINGKATKAN PENGETAHUAN DAN PEMAHAMAN ILMU TAJWID DI RTQ BIDAYATUN NASYIIN WARU SIDOARJO - Mirza Elmy Safira; Muhammad Yusron Maulana El-Yunusi; Chilyatun Nafis (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Santri development in Qur’anic learning, particularly in mastering tajwid, is essential to ensure accurate and proper recitation in accordance with the principles of tartil. However, many santri are able to read the Qur’an fluently without having sufficient understanding of tajwid rules. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aimed to improve santri’s knowledge and understanding of tajwid at Rumah Tahfidz Al-Qur’an (RTQ) Bidayatun Nasyi’in, Waru, Sidoarjo. The program employed the Participatory Action Research (PAR) approach, which involved planning, action, and evaluation stages conducted collaboratively. The activities were carried out for 14 days, from December 9 to December 22, 2025, through strengthening tajwid theory, practicing Qur’anic recitation with tartil, direct mentoring by teachers, and routine evaluations. The results indicated an improvement in santri’s understanding of makharijul huruf and recitation rules, as well as their ability to apply tajwid principles correctly in reading the Qur’an. Furthermore, the program enhanced active participation, learning discipline, and reinforced social and religious values within the RTQ environment. Therefore, santri development based on the PAR approach proved to be effective and transformative in improving the quality of Qur’anic recitation and tajwid comprehension in a sustainable manner.